Jumpy and Jerky: When Peripheral Vision Faces Reverse-Phi. (September 2020) - Lorenceau, Jean; Cavanagh, Patrick
When an annulus in fast apparent motion reverses its contrast over time, the foveal and peripheral percepts are strikingly different. In central vision, the annulus appears to follow the same path as an annulus without flicker, whereas in the periphery, the stimulus seems to randomly jump across the screen. The illusion strength depends on motion speed and reversal rate. Our observations suggest that it results from a balance between conflicting phi and reverse-phi motion, positional uncertainty, and attention. In addition to illustrating the differences between central and peripheral motion processing, this illusion shows that both discrete positional sampling and motion energy combine to generate motion percepts, although with eccentricity dependent weights that are themselves affected by attention.